Pengaruh Pajak Restoran terhadap Pendapatan Asli Daerah Kota Tasikmalaya - Ilah, Ilah; Aryansyah, Firman; Mustopa, Ujang Hasan; Haq, Haikal Matin (Universitas Galuh, 2025)
Revenue from the restaurant tax sector in Tasikmalaya Regency remains suboptimal due to non-compliance by several taxpayers. This study aims to analyze the contribution of restaurant tax to the Local Own-Source Revenue (PAD) of Tasikmalaya City from 2018 to 2022. A descriptive quantitative method was employed using secondary data over a five-year period. The findings indicate that both restaurant tax revenue and PAD fluctuated annually. Regression analysis revealed that restaurant tax had no significant effect on the PAD of Tasikmalaya City during the observed period. It is concluded that efforts to optimize restaurant tax collection must be strengthened to enhance its contribution to regional revenue.